Soluble tau aggregates, not large fibrils, are the toxic species that display seeding and cross‐seeding behavior. (19th October 2018) - Ghag, Gaurav; Bhatt, Nemil; Cantu, Daniel V.; Guerrero‐Munoz, Marcos J.; Ellsworth, Anna; Sengupta, Urmi; Kayed, Rakez
Abstract: Several studies have proposed that fibrillary aggregates of tau and other amyloidogenic proteins are neurotoxic and result in numerous neurodegenerative diseases. However, these studies usually involve sonication or extrusion through needles before experimentation. As a consequence, these methods may fragment large aggregates producing a mixture of aggregated species rather than intact fibrils. Therefore, the results of these experiments may be reflective of other amyloidogenic species, such as oligomers and/or protofibrils/short fibrils. To investigate the effects of sonication on the aggregation of tau and other amyloidogenic proteins, fibrils were prepared and well characterized, then sonicated and evaluated by various biochemical and biophysical methods to identify the aggregated species present. We found that indeed a mixture of aggregated species was present along with short fibrils indicating that sonication leads to impure fibril samples and should be analyzed with caution. Our results corroborate the previous studies showing that sonication of prion and Aβ fibrils leads to the formation of toxic, soluble aggregates. We also show that the oligomeric forms are the most toxic species although it is unclear how sonication causes oligomer formation. Recent results suggest that these small toxic oligomers produced by sonication, rather than the stable fibrillar structures, are prion‐like in nature displaying seeding and cross‐seeding behavior.